EFEKTIVITAS PELAKSANAAN PROGRAM PEMBANGUNAN PEDESAAN DI DESA KAUNERAN 1 KECAMATAN SONDER - OLBATA, APRILIA; RURU, JOORIE MARHAEN; PALAR, NOVIE ANDERS (JURNAL ADMINISTRASI PUBLIK, 2018)
The implementation of the Rural Development Program is one form of the government in developing villages. With rural development, it is expected that a change will occur in various aspects, including efforts to improve the welfare of the community through the pace of economic growth. The purpose of this study is to determine the level of effectiveness and the factors that influence it. To measure the level of effectiveness, researchers use three measures of effectiveness according to Ducan, who is quoted by Richard M. Steers in his book "Organizational Effectiveness" (2005), namely the level of achievement of objectives, integration, and adaptation to the Effectiveness of the Implementation of Rural Development Programs in Kauneran 1 Village, Sonder District. Researchers strive to be able to observe and analyze the development progress that has been planned. Among them by observing based on the results of interviews of 15 informants who are the village government, community figures, religious leaders, and the surrounding community. Based on the results of the study, it can be seen that with the development of the right target, it has increased the pace of the economy in the local community. Keywords : Effectiveness, Rural Development.